ANALISIS PELAKSANAAN DAN PENATAUSAHAAN DANA DESA PADA DESA-DESA DALAM WILAYAH KECAMATAN KOTAMOBAGU TIMUR, KOTA KOTAMOBAGU - Mamelo, Gresly Yunius Rainal; Kalangi, Lintje; Lambey, Linda (JURNAL RISET AKUNTANSI DAN AUDITING "GOODWILL", 2016)
Local autonomy authorizes local government to manage and operate their governance including villages as the smallest unit in supporting local development. UU number 16 year 2014 regulates villages and authorizes their local government to manage their own finance. Village fund management must be conducted in accordance with accountability, participatory and transparency as a responsibility fulfillment to public. This study is an exploratory qualitative research. Content analysis was used to analyzed data which consists of data reduction, data display and conclusion. Respondent villages are Moyag Village and Kobo Kecil Village in District of East Kotamobagu, Kotamobagu City. Results indicate that the implementation of village fund has been compiled in accordance to the regulation. However, there is a problem in the capability of human resources. Continuous trainings are needed to improve the capabilities of PTPKD and TPK Staff. On the other hand, computer application of SIMDA has been employed to administer the village fund, despite it has not been used optimally. Supervision for management staff is needed to improve the administration. Â  Keywords : Village Fund, Accountability, Participatory, Transparancy